Stigma and Discrimination for HIV/AIDS in the Health Sector: A Polish Perspective - Maria Gañczak (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2007)
The manifestations of the HIV/AIDS epidemic in Poland, as in other countries, have been received with stigmaand discrimination towards those living with the disease. The social implications of stigma are worsened whenthey hinder the provision of effective treatment by members of the health sector. One such limitation is theperceived need for mandatory HIV testing among hospital patients. This practice can violate the rights of thepatient and foster stigmatization. This quantitative study had as its main objectives to survey: 1) the degree offear of acquiring HIV at work among surgeons and surgical nurses, and 2) the impact of HIV/AIDS training andpractical experience with HIV patients on support for a testing policy of admitted patient and those who wouldundergo surgery among the same sample. Results evidence support for HIV testing of all inpatient admissionsin hospitals and pre-operative testing among both nurses and surgeons. Training on HIV matters can be animportant factor for lowering support for mandatory testing.